TOXICITY TEST OF KELAKAI LEAF EXTRACT (Stenochlaena palustris) TOWARD WISTAR RAT KIDNEY (Rattus norvegicus) - Hengki Robiyansyah; I Wayan Arya Krishnawan Firdaus; Deby Kania Tri Putri; Bayu Indra Sukmana; Erida Wydiamala (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Excessive free radicals cause oxidative stress which is dangerous for the body. The number of free radicals in the body can be controlled with the presence of antioxidants. Kelakai leaves (Stenochlaena palustris.) are known to have activity as an antioxidant which has the potential to become an ingredient in herbal medicine. Purpose: To prove whether there is a toxic effect of administering kelakai leaf extract on the kidneys of Wistar rats based on analysis of blood urea and creatinine levels. Method: A pure experimental study with a posttest-only with control group design method, there were 4 groups consisting of 1 negative control group and 3 treatment groups who were given kelakai leaf extract orally for 28 days and then analyzed the blood urea and creatinine levels of the Wistar rats. Results: The average values of urea and creatinine levels in the three treatment groups were still within the normal range. There was a significant difference in the urea levels of all groups (p<0.05), and there was no significant difference in the creatinine levels of treatment groups 2 and 3 (p>0.05). Conclusion: Kelakai leaf extract given orally for 28 days did not cause toxic effects on the kidneys of Wistar rats based on analysis of blood urea and creatinine levels.